2011
DOI: 10.1063/1.3548544
|View full text |Cite
|
Sign up to set email alerts
|

Carrier dynamics between delocalized and localized states in type-II GaAsSb/GaAs quantum wells

Abstract: Access and use of this website and the material on it are subject to the Terms and Conditions set forth at Carrier dynamics between delocalized and localized states in type-II GaAsSb/GaAs quantum wells Baranowski, M.; Syperek, M.; Kudrawiec, R.; Misiewicz, J.; Gupta, J.A.; Wu, X.; Wang, R.http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/jsp/nparc_cp.jsp?lang=fr L'accès à ce site Web et l'utilisation de son contenu sont assujettis aux conditions présentées dans le site LISEZ CES CONDITIONS ATTENTIVEMENT AVANT D'UTI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
17
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 16 publications
3
17
0
Order By: Relevance
“…4 and 5] heterostructures did not involve time-resolved spectroscopy, though this method allows exact determination of the optical transition type in such structures. 12,21 Up to now, there have been no works concerning temporal evolution of the PL spectra in GaAs/GaAsSb/InGaAs heterostructures, though in this heterosystem, as we show below, it is possible a) Email: krizh@ipmras.ru 0003-6951/2014/104(2)/021108/5/$30.00 V C 2014 AIP Publishing LLC 104, 021108-1 to substantially increase the PL signal at room temperature, as compared with GaAs/GaAsSb, which is important for the possible practical applications. The experimental data presented in this work allow determination of the ground state transition energy as a function of time delay, as well as the dynamics of carrier relaxation from the excited states.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…4 and 5] heterostructures did not involve time-resolved spectroscopy, though this method allows exact determination of the optical transition type in such structures. 12,21 Up to now, there have been no works concerning temporal evolution of the PL spectra in GaAs/GaAsSb/InGaAs heterostructures, though in this heterosystem, as we show below, it is possible a) Email: krizh@ipmras.ru 0003-6951/2014/104(2)/021108/5/$30.00 V C 2014 AIP Publishing LLC 104, 021108-1 to substantially increase the PL signal at room temperature, as compared with GaAs/GaAsSb, which is important for the possible practical applications. The experimental data presented in this work allow determination of the ground state transition energy as a function of time delay, as well as the dynamics of carrier relaxation from the excited states.…”
mentioning
confidence: 97%
“…3,10,11 The achievement of the emission wavelength 1.3 lm in GaAsSb/GaAs QW structures requires growing GaAsSb layers with Sb content about 0.36. 8,12 However, it is well known that the solubility limit of Sb in GaAsSb solid solution is about 0.27. 2,13 Therefore, growth of GaAsSb layers with Sb content about 0.36 can be realized only in nonequilibrium thermodynamic conditions.…”
mentioning
confidence: 99%
“…In GaAsBi alloys, the carrier localization is a well-known phenomenon, and the so called S-shape behavior can be seen in the temperature dependent PL under the low excitation conditions. 23,24 In addition, Baranowski et al 25,26 found that the PL kinetics are strongly influenced by the band bending effects as well as the carrier localization effects in type II GaAsSb/GaAs QWs using a time-resolved PL spectroscopy, suggesting that further investigations of the carrier localization phenomena in this InGaAs/GaAsBi QW are needed to evaluate its quality and perspectives for device applications. We believe that the underlying mechanism of the observations results from the band bending effect, which is intrinsic for the type-II band alignment of In 0.2 Ga 0.8 As/ GaAs 0.96 Bi 0.04 heterojunction, similar to the cases of GaAs/ GaAsSb 19 and InGaAs/GaAsSb.…”
mentioning
confidence: 99%
“…Over the past few decades, many III-V semiconductor materials and devices have been grown using molecular beam epitaxy (MBE) methods [90][91][92][93]. The properties of antimonide materials have been studied intensively.…”
Section: Discussionmentioning
confidence: 99%